Perancangan Sistem Informasi Reservasi Hotel Berbasis Website di Hotel Royal Asia Palembang - Ica Luo; Dedi Haryanto; Muhammad Ihsan (Lembaga Pengembangan Kinerja Dosen, 2025)
The room reservation process at Hotel Royal Asia Palembang is still carried out manually, requiring customers to visit the hotel directly to make a booking. This method is inefficient as it consumes additional time, effort, and costs, particularly for customers who live far from the hotel. To address this issue, this study aims to design and develop a web-based hotel reservation information system that enables customers to make bookings online. The system was developed using the PHP programming language and MySQL as the database, while the Unified Modeling Language (UML) was utilized as a tool for system design. Through this system, customers can easily make room reservations online by selecting the desired check-in and check-out dates without the need to visit the hotel in person. Moreover, the system assists hotel management in organizing reservation data, room availability, and customer information in an integrated manner. The testing results indicate that the developed online hotel reservation information system functions effectively and provides convenience, efficiency, and improved service quality for Hotel Royal Asia Palembang customers.